Acilação e alquilação fotoquímica de heteroarenos utilizando diacetil - Dantas, Juliana Arantes (Universidade Federal de São Carlos, 2018)
N-heterocycles are important building blocks in the synthesis of bioactive compounds, besides that many of them are present in natural products. Most of the methodologies for heteroarene functionalization requires several steps and drastic conditions, thus increasingly it has been reported shorter synthetic routes. C-H activation has emerged with this purpose and can also be applied in the sustainable chemistry area. Thus, in this work it was developed a mild photoinduced C-H activation, free of oxidants and transition metals, of N-heteroarenes incorporating acyl and cetyl groups. In the scope, 2-methylquinolines, 2-methylquinoxalines and 2-methylquinazolines were investigated. The best results were obtained with 2-methylquinolines, leading to a series of derivatives with good to moderated yields. It was also carried out a mechanistic study in order to understand how this reaction proceeds. Furthermore, the synthesized compounds were evaluated against the parasite Plasmodium falciparum, using as standards chloroquine and primaquine, which are current drugs to treat malaria.
Photochemistry acylation and alkylation of azarenes with diacetyl
Keywords: Fotoquímica; Reação tipo Norrish; Química verde; Livre de metais de transição; CIENCIAS EXATAS E DA TERRA::QUIMICA